Early Christian doctrines - Kelly, J. N. D. (John Norman Davidson) (London Adam & Charles Black, 1965)
This revised edition of the standard history of the first great period in Christian thought has been thoroughly updated in the light of the latest historical findings. Dr. Kelly organizes an ocean of material by outlining the development of each doctrine in its historical context. He lucidly summarizes the genesis of Chrisitian thought from the close of the apostolic age to the Council of Chalcedon in the fifth century--a time teeming with fresh and competing ideas. The doctrines of the Trinity, the authority of the Bible and tradition, the nature of Christ, salvation, original sin and grace, and the sacraments are all extensively treated in these pages. --
Prolegomena. The background ; Tradition and Scripture ; The holy Scriptures -- The pre-Nicene theology. The divine triad ; Third-century Trinitarianism ; The beginnings of Christology ; Man and his redemption ; The Christian community -- From Nicaea to Chalcedon. The Nicene crisis ; The doctrine of the Trinity ; Fourth-century Christology ; The Christological settlement ; Fallen man and God's grace ; Christ's saving work ; Christ's mystical body ; The later doctrine of the sacraments -- Epilogue. The Christian hope -- Mary and the saints
Includes bibliographical references and index
Keywords: Theology, Doctrinal -- History -- Early church, ca. 30-600